Peranan Painting Bali sebagai Cendramata Khas Bali - I Gusti Ketut Indra Pranata Darma (UHN IGB Sugriwa Denpasar, 2019)
There are a lot of factors that make a product can be categorized as a souvenir typical of a region. Among them is having the distinctiveness of a place or unique, can be carried by hand, relative price, has a value of reminiscence, is able to be awarded andhave the memory of events from somewhere. Typical regional products Gianyar one of them is Painting fabrice. This study aims to determine whether painting fabrics fulfills the criteria for a souvenir and development efforts. The study was conducted using qualitative method by conducting depth interviews with informants. Informants are looking for is a trader and craftsmen painting fabric, and buyers who frequently use the product painting fabrics. Based on research data obtained, painting fabrics can becalled as souvenirs of the Bali because it has a strong characteristic 5 of the 6 available. For development efforts that have been made for this, among others, by utilizing technology to introduce the product, participated in the exhibition to get a new variationof the motif.